2021
DOI: 10.3390/app11020722
|View full text |Cite
|
Sign up to set email alerts
|

3D Gravity Inversion on Unstructured Grids

Abstract: Compared with structured grids, unstructured grids are more flexible to model arbitrarily shaped structures. However, based on unstructured grids, gravity inversion results would be discontinuous and hollow because of cell volume and depth variations. To solve this problem, we first analyzed the gradient of objective function in gradient-based inversion methods, and a new gradient scheme of objective function is developed, which is a derivative with respect to weighted model parameters. The new gradient scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The geophysical methods such as gravity and magnetic are usually implemented by the 2D grid because they use simple equipment and are the cheapest. The inversions of these methods were developed in 2D and 3D framework architecture [33]. ERT and CSAMT measure electrical resistivity with a unit of Ωm.…”
Section: Geophysical Surveysmentioning
confidence: 99%
“…The geophysical methods such as gravity and magnetic are usually implemented by the 2D grid because they use simple equipment and are the cheapest. The inversions of these methods were developed in 2D and 3D framework architecture [33]. ERT and CSAMT measure electrical resistivity with a unit of Ωm.…”
Section: Geophysical Surveysmentioning
confidence: 99%
“…Finally, since geophysical inversion products are generally used as part of the interpretation process that seeks to differentiate geologic units, several authors have recently suggested the use of a clustering constraint that pushes the inversion process to select models primarily composed of a number of expected discrete rock units. The fuzzy c-means algorithm has been used in the context of seismic tomography (Sun & Li 2015), gravity inversion (Sun et al 2001), and seismic inversion (Kieu & Kepic 2020). Whilst such constraints have shown great promise and helped the solution to be more consistent with geological prior knowledge of the subsurface, the clustering algorithm has a local effect and cannot be informed with spatial information of nearby subsurface locations.…”
Section: O R I Gmentioning
confidence: 99%